2023
DOI: 10.1093/femsyr/foac067
|View full text |Cite
|
Sign up to set email alerts
|

Grape-associated fungal community patterns persist from berry to wine on a fine geographical scale

Abstract: Wine grape fungal community composition is influenced by abiotic factors including geography and vintage. Compositional differences may correlate with different wine metabolite composition and sensory profiles, suggesting a microbial role in the shaping of a wine's terroir, or regional character. While grape and wine-associated fungal community composition has been studied extensively at a regional and sub-regional scale, it has not been explored in detail on fine geographical scales over multiple harvests. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…The statistically significant association between bacterial composition and fermentation stage suggested the possible occurrence of an ecological succession throughout agave fermentation, aligning with findings from other fermentation processes , Boynton and Greig 2016, Liu et al 2020, Martiniuk et al 2023). However, in agave fermentations, the changes in fungal composition may be more subtle compared to other systems.…”
Section: Different Bacterial and Fungal Community Dynamics During Aga...supporting
confidence: 85%
See 1 more Smart Citation
“…The statistically significant association between bacterial composition and fermentation stage suggested the possible occurrence of an ecological succession throughout agave fermentation, aligning with findings from other fermentation processes , Boynton and Greig 2016, Liu et al 2020, Martiniuk et al 2023). However, in agave fermentations, the changes in fungal composition may be more subtle compared to other systems.…”
Section: Different Bacterial and Fungal Community Dynamics During Aga...supporting
confidence: 85%
“…Changes in the taxonomy of microorganisms also explained some of the discrepancies with previous reports as was the case for Zymomonas. Comparing the microbial diversity of agave fermentations with that of other fermented foods and beverages, the bacterial diversity (Shannon index) is close to average diversity in other fermentations, while fungal diversity is closer to the least diverse environments such as wine fermentations (Leech et al 2020, Kharnaior and Tamang 2023, Martiniuk et al 2023, Qi et al 2023. Overall, our work sets the basis for a more comprehensive understanding of the composition and diversity of the microbial communities responsible for the fermentation needed to produce traditional agave spirits.…”
Section: A Country-wide Analysis Of Microbial Diversity In Traditiona...mentioning
confidence: 99%
“…In fact, bacterial populations vary greatly between batches of agave juice and during fermentation (Aldrete-Tapia et al, 2019). Martiniuk et al (2023) recently examined fungal communities on the surface of grapes, crushed grapes, and during spontaneous fermentation in Pinot Noir vineyards in British Columbia's Okanagan Valley wine region. The study found that fungal populations varied significantly between vineyards, vineyard blocks, and vintages, with each vineyard displaying a distinctive fungal community signature.…”
Section: Influence Of Yeast Interaction On Aromatic Compounds and The...mentioning
confidence: 99%
“…The grapevine ( Vitis vinifera ) phyllosphere is colonized by bacteria and fungi that substantially modulate grapevine health, fruit development and ripening, as well as the quality of grapes and wine ( Barata et al, 2012 ; Martiniuk et al, 2023 ). The microbiome of a grapevine plant has direct and indirect relationships with its host and specific microbial biodiversity linked to a particular vineyard location is reported to be a crucial aspect, in conjunction with edaphic, climatic and human factors, in the concept of wine terroir ( Gilbert et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%